Identification of biomarkers correlated with hypertrophic cardiomyopathy with co‐expression analysis. Issue 12 (6th May 2019) - Chen, Ran; Ge, Tiantian; Jiang, Wanying; Huo, Junyu; Chang, Qing; Geng, Jie; Shan, Qijun
Abstract: Hypertrophic cardiomyopathy (HCM) is reported to be the most common genetic heart disease. To identify key module and candidate biomarkers correlated with clinical prognosis of patients with HCM, we carried out this study with co‐expression analysis. To construct a co‐expression network of hub genes correlated with HCM, the Weighted Gene Co‐expression Network Analysis (WGCNA) was performed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed by Database for Annotation, Visualization and Integrated Discovery (DAVID). The protein‐protein interaction network analysis of central genes was performed to recognize the interactions of central genes. Gene set enrichment analyses were carried out to discover the possible mechanisms involved in the pathways promoted by hub genes. To validate the hub genes, quantitative real‐time polymerase chain reaction (RT‐PCR) was performed. Based on the results of topological overlap measure based clustering, 2, 351 differentially expressed genes (DEGs) were identified. Those genes were included in six different modules. Of these modules, the yellow and the blue modules showed a pivotal correlation with HCM. DEGs were enriched in immune system procedure associated GO terms and KEGG pathways. We identified nine hub genes (TYROBP, STAT3, CSF1R, ITGAM, SYK, ITGB2, LILRB2, LYN, and HCK) affected the immune system significantly. Among the genes we validated with RT‐PCR, TYROBP, CSF1R, and SYK showed significant increasing expression levels in model HCM rats. In conclusion, we identified two modules and nine hub genes, which were prominently associated with HCM. We found that immune system may play a crucial role in the HCM. Accordingly, those genes and pathways might become therapeutic targets with clinical usefulness in the future. Abstract : We used the weighted gene co‐expression network analysis (WGCNA) to identify hub genes correlated with hypertrophic cardiomyopathy (HCM). We found that immune system process may play a crucial role in HCM, and we validated several genes with real‐time polymerase chain reaction (RT‐PCR).